Keragaman Komunitas Moluska di Wilayah Hutan Mangrove Kawasan Pulau Dua Provinsi Banten - Anas Lutfi; Wida Putri Pramudita; Nurul Khotimah; Nisah Afifah; Setyoko Setyoko (Universitas Hasanuddin, 2023)
Mollusca it is a soft, non-metabolic, symmetrical animal. That is, it usually has considerable adaptive ability and ACTS asan environmental indicator. The study's objectives were to understand (1) the variety of its phyla that may be found on the second island sanctuary, banten, (2) its quantity, and (3) the variables that influenced the abundance of the philum reserca there. On April 23, 2022, the study was conducted in the mangrove preserves of the two coastal islands, the banten, while under attack. Data retrieval was carried out via a transfer mechanism that was utilized by two different stations. A natural and secondary location in the adjacent ponds is Station 1 on the second island sanctuary. Each station has three 10-m (10-m) modules, each with three 1-by-1-meter graphs for examples of astronomical measurements. About study demonstrating the value of the current population index at both sites, including low H'1, existence of four molluscan species. At station 1, there are 3 transplants, 1 species of Cerithidea Quoyii, 2 species of Crossing Coffea, 7 species of Floridobia sp., 1,253 species, and 24 species of Milax Sowerbyi. At station 2 each - the average version of the cerithidea quoyii only has 51. The diversity index at station I was 0.2, higher than the corresponding figure at station II, which was 0. Thus, the uniformity value at station I was 0.14, whereas the uniformity value at station II was 0. At station I, the dominance index was 0.92, while at station II, it was 1.